A Theoretical Study on STEM Education: Proposal of Two Applications - Arıkan, Elif Esra; Arıkan, Elif Esra (My University, 2018)
As communication technology develops rapidly in the 21st century, it is easy to reach knowledge. At this point students should be able to create their own knowledge by researching, analyzing and synthesizing rather than asking the questions they can reach via internet. Real life problems may not be solved according to a single discipline. Therefore, it would be beneficial for us to transfer the climate and teamwork to the disciplines as a whole for the students. The purpose of this study is to present the importance and unexplained parts of STEM education through literature scan and especially to suggest STEM practices which mostly deal with mathematics classes. This study is a theoretical study and document analysis technique from qualitative research methods was used in the study. The study was prepared in terms of theory and it was presented to be an example for the other researchers. There are two sample practices together with their objectives in this study. While SCRATCH coding program was used in one of the applications and the other application was structured on isoperimetric theorem.

21. Yüz yılda iletişim teknolojisi hızla geliştiği için bilgiye ulaşmak kolaylaşmaktadır bu noktada öğrencilere internet üzerinden ulaşabilecekleri sorular sormak yerine araştırarak analiz ederek ve sentezleyerek kendi bilgilerin oluşturmalarına fırsat verilmelidir. Gerçek yaşamda birçok değişkenden oluşan bir problemle karşılaşan öğrencilere, derslerde tek bir değişken üzerinden problem çözmeyi öğretmek gerçek yaşamla okul dersleri arasında uçurum oluşturacaktır. Gerçek yaşam problemleri tek bir disipline göre de çözülemeyebilir. Dolayısıyla öğrencilere disiplinleri bir bütün olarak ele alma iklimini ve ekip çalışmasını aktarmamız faydalı olacaktır. Bu çalışmanın amacı, STEM eğitiminin önemini ve açıklanamayan kısımlarını literatür taraması ile sunmak ve özellikle matematik dersleriyle ilgilenen STEM uygulamalarını önermektir. Bu çalışma teorik bir çalışmadır ve çalışmada nitel araştırma yöntemlerinden elde edilen doküman analiz tekniği kullanılmıştır. Çalışma teorik açıdan hazırlanmış ve diğer araştırmacılar için örnek teşkil etmesi adına sunulmuştur. Çalışmada iki örnek uygulama kazanımları ile birlikte yer almaktadır. Uygulamalardan birinde SCRATCH kodlama programı kullanılmış ve diğer uygulama izoperimetrik teoride yapılandırılmıştır.
STEM Eğitimi Üzerine Bir Teorik Çalışma: İki Uygulama Önerisi
Keywords: STEM education; Engineering; Mathematics-based STEM; Scratch; Coding; Isoperimetric theory; STEM eğitimi; Mühendislik; Matematik ağırlıklı STEM; Scratch; Kodlama; İzoperimetrik teorem